Protecting Children from The Internet Risks: A Perspective from Children and Caregivers in The Capital of Jordan- Amman - Essra Fawzy Mostafa Al-Eer (Journal of Psychology and Behavior Studies, 2025)
The study aimed to protect children from online risks in the capital of Jordan-Amman from the perspectives of both children and caregivers during the year (2023-2024). This was achieved by identifying the online risks faced by children, and exploring the protective mechanisms against various types of risks. The study adopted a descriptive-analytical approach, collecting information through interviews with (30) children and (30) caregivers in the capital of Jordan-Amman. The findings highlighted an increasing and evolving nature of online risks, with negative impacts posing a threat to the psychological and emotional well-being of children. The study emphasized the need for the development and updating of protection mechanisms. The children's consensus on risks identified awareness of risks, electronic games, and chat as the most hazardous in terms of communication with strangers, their distracting effects, and potential health risks. Risks related to content and sources, as well as internet access, that were followed. Caregivers were found to play a moderate role in protection, linked to various areas, by adhering to digital awareness and safety standards. In conclusion, specific protection mechanisms were suggested based on the study's results, aiming to assist caregivers and children in Jordan to apply these mechanisms to mitigate the internet risks.